2005
DOI: 10.1016/j.rapm.2005.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of the Brachial Plexus Block via the Posterior Approach

Abstract: This study reports the clinical effectiveness of the single-injection nerve-stimulation technique for the brachial plexus block via the posterior approach in patients undergoing shoulder surgery. It appears to be effective, relatively safe, and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2005
2005
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…The interscalene brachial plexus block, described by Winnie (lateral approach) is more commonly used in shoulder surgeries [5][6][7][8][9] . Some alternatives to the Winnie technique have been proposed and, among them, the posterior brachial plexus block has been shown to be safe and effective [9][10][11][12][13][14][15][16] . A prior study observed that the Table II use of 20, 30, or 40 mL of local anesthetic in the posterior approach promoted similar postoperative analgesia 13 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interscalene brachial plexus block, described by Winnie (lateral approach) is more commonly used in shoulder surgeries [5][6][7][8][9] . Some alternatives to the Winnie technique have been proposed and, among them, the posterior brachial plexus block has been shown to be safe and effective [9][10][11][12][13][14][15][16] . A prior study observed that the Table II use of 20, 30, or 40 mL of local anesthetic in the posterior approach promoted similar postoperative analgesia 13 .…”
Section: Resultsmentioning
confidence: 99%
“…A técnica de bloqueio do plexo braquial, por via interescalênica, descrita por Winnie (abordagem lateral) é a mais utilizada para intervenções cirúrgicas no ombro [5][6][7][8][9] . Algumas alternativas à técnica de Winnie têm sido propostas, dentre elas, a abordagem do plexo braquial pela via posterior se demonstrou ser segura e eficaz [9][10][11][12][13][14][15][16] . Em estudo anterior, foi observado que a utilização de volumes de anestésico de 20, 30 ou 40 mL na abordagem posterior promove analgesia pós-operatória semelhante 13 .…”
Section: Discussionunclassified
“…After a slight needle adjustment, muscle contractions were produced. Needle placement was accurate in a median [range] of 2 [1][2][3][4] attempts. In nine patients, the brachial plexus was found at the first attempt.…”
Section: Resultsmentioning
confidence: 99%
“…The technique performed in this case has been used by several authors without producing significant complications [5–7]. However, the accidental production of spinal anaesthesia has been reported as a complication of attempted brachial plexus blockade using the posterior approach [11].…”
Section: Discussionmentioning
confidence: 99%
“…[6]. The posterior approach has been shown to be effective, relatively safe and well tolerated by patients [7]. In this report, we describe a patient who developed the symptoms and signs of high epidural anaesthesia after an attempted brachial plexus blockade by the posterior approach.…”
mentioning
confidence: 99%